Burnout among teachers and its relationship with some variables in Lattakia - Twalu, Nadine (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The research aims to identify the burnout level among teachers of the second cycle of basic education in the province of Latakia, the study of differences between them in the burnout level depending on the set of variables represented by: sex, place of residence, and the number of years of experience, educational qualification. Adopted researcher descriptive method, was used Maslak scale to measure burnout level, where it was distributed to a sample of teachers of (369) teachers have been them (321), and a response rate (86.99%), and using appropriate statistical methods was reached following results: 1- The combustion psychological dimension of stress on emotional level is the level of the average, with regard to sag Bbaadi feelings, and a lack of sense of accomplishment is weak, where teachers feel a high degree of achievement. 2- There are significant differences between the mean scores of teachers to burnout scale dimensions variable depending on sex, and these differences in favor of females parameters. 3- The lack of statistically significant differences between the mean scores of teachers to burnout scale dimensions variable depending on the place of residence. 4- The lack of statistically significant differences between teachers in the dimensions of emotional stress and feelings sag depending on the variables of the number of years of experience and educational qualification, while the existence of differences in the lack of a sense of accomplishment after the show depending on the variables of the number of years of experience and educational qualification.